Experiencias narrativas de niños, niñas y adolescentes en condición de discapacidad intelectual en su entorno escolar del Comité de Rehabilitación de Antioquia (2021)
This research starts from a need to constantly search for the well-being of the population with Intellectual Disability (ID) of the program called “Apoyo a la Inclusión Educativa del Comité de Rehabilitación de Antioquia”. The research aims to understand the narrative experiences of children and adolescents about inclusive education processes, as well as the various integration practices in the school context. The methodology used is qualitative, under a narrative approach, which makes it possible to understand not only situations, facts or phenomena, but also facilitates a broader approach to information and understanding of reality. Consequently, a categorical analysis of the narratives is carried out, through the experiences told by nine children with intellectual disabilities in their school environment and their families. From this, it was possible to identify some variables that students present within Educational Institutions, such as absence of teachers from supportive or suitable classrooms in the face of their disability, little participation, rejection, ridicule and discrimination coming from their peers. It was possible to recognize the importance of managing the emotions that children present in schools and the value it has as a plan for improvement and opportunities to optimize their living conditions. In turn, there were found weaknesses in families and schools in the face of the due processes that they must carry out to guarantee an inclusive education